Incidence of Chorioamnionitis in preterm deliveries at Northern Indian hospital: A prospective study - Sharma, Dr. BR; Dogra, Dr. Poojan; Kaushal, Dr. Sushruti; Sharma, Dr. Reena; Tanupriya, Dr. (Asian Journal of Medical Research, 2018)
Background: Objective: Preterm birth is a major obstetric problem, which is associated with high perinatal mobidity and mortality. Genital infection is postulated to play an important role in preterm delivery. We planned to study genital infections as a cause of preterm delivery. Subjects and Methods: This study was conducted in Department of Obstetrics and Gynecology, Kamla Nehru State Hospital for Mother and Child IGMC Shimla, on 200 women attending antenatal outpatient department over one year. After history and investigations, blood samples were taken for TLC &CRP. High vaginal swab was sent for culture and Nugent scoring for bacterial vaginosis. Placenta was sent histo-pathological examination. Tissue samples from each placenta and roll of membranes from rupture point to placental margin were sent for bacterial culture. Results: History of preterm birth is a significant risk factor for preterm delivery. Increased TLC and Positive vaginal culture were significantly associated with preterm delivery. CRP was not found significantly associated with preterm delivery. Presence of clue cells and gram negative bacilli on vaginal smears as a marker of bacterial vaginosis had significant association with preterm birth. Histological evidence of chorioamnionitis in placenta as well as grade of chorioamnionitis was associated with preterm delivery. Conclusion: Genital infections, in the form of bacterial vaginosis and chorioamionitis, are significant causes of preterm delivery.